System-level policies on appropriate opioid use, a multi-stakeholder consensus - Patrice Forget; Champika Patullo; Duncan Hill; Atul Ambekar; Alex Baldacchino; Juan Cata; Sean Chetty; Felicia J. Cox; Hans D. de Boer; Kieran Dinwoodie; Geert Dom; Christopher Eccleston; et al. (BMC, 2022)
Abstract Background This consensus statement was developed because there are concerns about the appropriate use of opioids for acute pain management, with opposing views in the literature. Consensus statement on policies for system-level interventions may help inform organisations such as management structures, government agencies and funding bodies. Methods We conducted a multi-stakeholder survey using a modified Delphi methodology focusing on policies, at the system level, rather than at the prescriber or patient level. We aimed to provide consensus statements for current developments and priorities for future developments. Results Twenty-five experts from a variety of fields with experience in acute pain management were invited to join a review panel, of whom 23 completed a modified Delphi survey of policies designed to improve the safety and quality of opioids prescribing for acute pain in the secondary care setting. Strong agreement, defined as consistent among> 75% of panellists, was observed for ten statements. Conclusions Using a modified Delphi study, we found agreement among a multidisciplinary panel, including patient representation, on prioritisation of policies for system-level interventions, to improve governance, pain management, patient/consumers care, safety and engagement.